A Longitudinal Analysis of Doctoral Graduate Supply in the Educational Measurement Field. Issue 1 (4th September 2020) - Randall, Jennifer; Rios, Joseph A.; Jung, Hyun Joo
Abstract: For nearly three decades, researchers have been concerned that the educational measurement field is not producing enough graduate‐level specialists to meet the growing demand driven by the increased use of educational assessments in the United States. This study examined the supply‐side aspect of the proposed labor shortage by relying on data from the National Science Foundation's Survey of Earned Doctorates collected between 1997 and 2016. Over the 20 years examined, measurement programs produced 3, 124 doctoral graduates, and across this time span, the annual production of graduates nearly doubled. This supply expansion can largely be attributed to the increase in the number of international graduates, which outpaced the annual growth rate of domestic PhD recipients by 156%. Moreover, 85% of graduates were found to either self‐identify as White or Asian. Less than 10 Hispanic and no more than 20 Black graduates were produced in any of the years examined. Of the 76% of graduates that reported having a job offer or accepted a position upon graduation, most entered the academy despite the overall average starting salary (59, 484) being considerably lower than the starting salary for their counterparts entering industry (84, 918), government (69, 970), or other educational institutions (81, 428).